The English Language Needs for Information Technology: A Comparison Case of Professionals and Students - Rizky Eka Prasetya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
English has established itself as a global lingua franca. The global growth in the usage of English has resulted in many reforms within educational institutions. The study aims to ascertain and examine English needs for information technology purposes among professionals and learners on a wide scale. A quantitative descriptive approach with a survey research design was employed in the study, and it applied to the Cross-Sectional survey design. Mailed questionnaires were collected from 243 students’ and 23 professionals. According to the questionnaires, the result found that professional purposes for learning English are to complete written-project reports or papers, while students must communicate with the global community. The English learning outcome implied different aims. The professionals want to complete language instructions for information technology processing, but students expect information access to the products. Professional speaking abilities are concerned with asking clarifications in the group or personal meetings, yet students concern more in taking and receiving the phone calls. In the same manner as writing, professionals and students have the same expectation that is to produce formal reports in academic or professional situations. Both participants perceive the responses by reading ability concerned to the summarizing detail information. This study affirmed an interrelation between the English standing in professional IT and students’ IT positions in communication experiences in their present circumstances.